Revisiting the Communicative Approach: Addressing Common Misconceptions - Mohammed Nurul Islam (An Overview of Literature, Language and Education Research Vol. 2, 2024)
Though Communicative Language Teaching (CLT) is acknowledged by the National Curriculum & Textbook Board (NCTB) and many English teachers as one of the most effective approaches to English language teaching in Bangladesh, there are still a number of misconceptions about it. Addressing these misconceptions is crucial because they can lead to ineffective teaching practices and hinder learners’ progress in developing true communicative competence. By comparing the perspectives of Johnstone, Sato, Kleinsasser, Thompson, and Spada, this article focuses on four main misconceptions commonly held by language teachers and researchers. Highlighting and correcting these misunderstandings can enhance the implementation of CLT, ultimately benefiting both educators and learners by fostering more accurate and effective language teaching strategies.